Glucocorticoid Tapering: a Literature Review - Damayanti, Nurul; Sumarno, Sumarno (Journal of Islamic Pharmacy, 2020)
Glucocorticoids (GCs), a class of corticosteroids that widely used a variety of diseases, associated physiological processes in the body [1,2]. It has structurally and pharmacologically similar to the endogenous hormone cortisol with various beneficial functions like anti-inflammatory, immunosuppressive, anti-proliferative, and vasoconstrictive effects. As an anti-inflammatory and immunosuppressive effect, corticosteroids through a combination of both inhibition upregulation of gene transcription [3-5]. Despite beneficial effects, they also have side effects that depend on the dose, type of steroid and length of treatments [6]. Short courses of high-dose GCs usually are safe and reasonably well-tolerated, but they do have numerous potential adverse effects [7]. Many of the severe complications occur in long-term use at doses greater than 20 mg of prednisone per day for three weeks or more causes tertiary adrenal insufficiency due to the HPA-axis (Hypothalamic Pituitary Adrenal Axis) suppression by endogenous GCs [8-10]. In this article, we’ll discuss how to manage GCs tapering and when is the right time to use GCs.